Эпидемиологические особенности рака шейки матки - Рузибоева, Е. Р.; Каримов, А. Р. (БНТУ, 2021)
Cervical cancer (CC) is one of the most common malignant neoplasms, ranking 4th in terms of morbidity and mortality among women [1]. More than 500 thousand patients with cervical cancer are registered annually in the world, half of whom die during the first year due to late diagnosis and a high proportion (46 %) of advanced forms of the disease [1, 4].